Reactogenicity and Immunogenicity Against MPXV of the Intradermal Administration of Modified Vaccinia Ankara Compared to the Standard Subcutaneous Route - Valentina Mazzotta; Pierluca Piselli; Alessandro Cozzi Lepri; Giulia Matusali; Eleonora Cimini; Rozenn Esvan; Francesca Colavita; Roberta Gagliardini; Stefania Notari; Alessandra Oliva; Silvia Meschi; Rita Casetti; et al. (Vaccines)
Background: The recent resurgence of mpox in central Africa has been declared a new public health emergency of international concern (PHEIC) requiring coordinated international responses. Vaccination is a priority to expand protection and enhance control strategies, but the vaccine’s need exceeds the currently available doses. Intradermal (ID) administration of one-fifth of the standard modified vaccinia Ankara (MVA-BN) dose was temporarily authorized during the 2022 PHEIC. Studies conducted before 2022 provided evidence about the humoral response against the vaccinia virus (VACV) after vaccination but not against the mpox virus (MPXV). Moreover, no data are available on the T-cell response elicited by MVA-BN administered subcutaneously or intradermally. Methods: We compare the two vaccine administration routes according to reactogenicity (n = 943) and immunogenicity (n = 225) of vaccine recipients attending INMI Spallanzani hospital during the 2022 vaccination campaign in Rome, Italy. Results: We found that the ID route elicited higher titers of MPXV-specific IgG (mean difference of 0.26 log2, p = 0.05) and nAbs (0.24 log2, p = 0.08) than the subcutaneous (SC) route one month after the complete vaccination cycle. At the same time, no evidence for a difference in cellular response was found. Conclusions: MVA-BN was globally well tolerated despite higher reactogenicity for the ID than the SC route, especially for the reactions at the local injection site. The ID dose-sparing strategy was proven safe and immunogenic and would make vaccination available to more people. Our data support the current WHO recommendation of using the ID route in low–medium-income countries (LMIC), although response data in people infected with the new 1b clade are urgently needed.